A SYSTEM DYNAMICS MODEL ASSESSING THE SUSTAINABILITY OF THE PERFORMANCE OF SUPPLY CHAINS WITH REVERSE FLOW - Abdallah, Khaled S.; M. El-Beheiry, Mohamed (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
Sustainability in supply chains is more important than ever. In this paper, we consider a supply chain with a reverse flow where customers can return or replace products that flow backward to upstream members. The returned products re-enter the forward flow after different adjustments. We focus on measuring how the different operational parameters affect the sustainability of the supply chain and whether their interaction may affect the sustainability measures or not. The sustainability dimensions considered here are the social and environmental dimensions. A system dynamics model is developed for a supply chain with reverse flow. The proposed model measures the social dimension in terms of customer satisfaction and the environmental dimension in terms of the green image factor. We run the model for different parameters, and a factorial analysis is conducted on the results to show their main effect and their interaction effect on the measures under study. The results show how each of the main factors affects the sustainability of the supply chain; and how the interactions between the different factors can improve the already conflicting nature between the environmental and social performance measures.